2019
DOI: 10.1186/s41256-019-0119-x
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers

Abstract: Background Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The study suggested two primary findings: that women in the study did not report feelings of discrimination in health workplaces, and that senior health-sector women are perceived as more in tune with women-centric issues, defined in the research as policies that address concerns disproportionately affecting the health and well-being of the female sex (Sawadogo-Lewis et al 2018). A second paper from this study found that interviewees unanimously argued that women's health is sufficiently prioritised in national health policies and strategies in Mozambique, but that the problem was implementation of these policies and strategies (Qiu et al 2019). What we can draw from these findings is that, descriptively at least, women in the professionalised decision-making areas of the health systemthat is women with intersecting attributes of education, training, and socioeconomic statusare quite insistent that at a personal level they do not face gender-related barriers in the health workplace.…”
Section: Mozambique Gender Context: Brief Overviewmentioning
confidence: 88%
“…The study suggested two primary findings: that women in the study did not report feelings of discrimination in health workplaces, and that senior health-sector women are perceived as more in tune with women-centric issues, defined in the research as policies that address concerns disproportionately affecting the health and well-being of the female sex (Sawadogo-Lewis et al 2018). A second paper from this study found that interviewees unanimously argued that women's health is sufficiently prioritised in national health policies and strategies in Mozambique, but that the problem was implementation of these policies and strategies (Qiu et al 2019). What we can draw from these findings is that, descriptively at least, women in the professionalised decision-making areas of the health systemthat is women with intersecting attributes of education, training, and socioeconomic statusare quite insistent that at a personal level they do not face gender-related barriers in the health workplace.…”
Section: Mozambique Gender Context: Brief Overviewmentioning
confidence: 88%
“…Relatedly, misoprostol was also very infrequently available, and many APEs reported never having had it at all. Although women's health is prioritized at the policy level in Mozambique (20), breakdowns in the supply chain such as those found here threaten potential gains in women's health.…”
Section: Medication and Commoditiesmentioning
confidence: 88%
“…The governmental initiatives and strategic plans to improve maternal health indicate support from the government and desire to address obstacles to maternal health services [19]. Indeed, while women's health (including maternal health) is being prioritized, gains in women's health have been modest due to in part to poor implementation of government policies [29].…”
Section: Discussionmentioning
confidence: 99%